IMPLEMENTASI STRING MATCHING DENGAN ALGORITMA BOYER-MOORE UNTUK MENENTUKAN TINGKAT KEMIRIPAN PADA PENGAJUAN JUDUL SKRIPSI/TA MAHASISWA (STUDI KASUS: UNIVERSITAS XYZ) - Imam Ahmad; Rohmat Indra Borman; Gavan Gorbi Caksana; Jafar Fakhrurozi (SINTECH (Science and Information Technology) Journal, 2021)
In determining the research topic as well as the title for the Thesis / TA, it is possible that there will be a similarity in the title between one student and another, whether intentionally or unintentionally. For this reason, the Study Program must check the titles submitted by students, so as to avoid indications of similar titles and indications of plagiarism. Efforts that can be made to make it easier to check the Thesis title are by performing string matching on the text on the title that will be submitted by students. One of the string matching algorithms is Boyer-Moore. Boyer-Moore, who made the match starting from the rightmost character then left based on the value of the occurrence heuristic (HO) and match heuristic (MH) in determining the shift. This research produces a system that is able to determine the similarity of the proposed Thesis titles based on the existing title repositories. From the results of testing the processing time by entering 100 and its multiples show that the Boyer-Moore algorithm is able to match quickly. The results also showed that the more data the more time it took, but the average increase in time only increased by 34%.